Design and Evaluation of the Initial 50th Percentile Female Prototype Rear Impact Dummy, BioRID P50F – Indications for the Need of an Additional Dummy Size - Carlsson, Anna; Davidsson, Johan; Linder, Astrid; Svensson, Mats Y. (Frontiers in Bioengineering and Biotechnology, 2021)
The objective of this study was to present the design of a prototype rear impact crash test dummy, representing a 50th percentile female, and compare its performance to volunteer response data. The intention was to develop a first crude prototype as a first step towards a future biofidelic 50th percentile female rear impact dummy. The current rear impact crash test dummy, BioRID II, represents a 50th percentile male, which may limit the assessment and development of whiplash protection systems with regard to female occupants. Introduction of this new dummy size will facilitate evaluation of seat and head restraint (HR) responses in both the average sized female and male in rear impacts. A 50th percentile female rear impact prototype dummy, the BioRID P50F, was developed from modified body segments originating from the BioRID II. The mass and rough dimensions of the BioRID P50F is representative of a 50th percentile female. The prototype dummy was evaluated against low severity rear impact sled tests comprising six female volunteers closely resembling a 50th percentile female with regard to stature and mass. The head/neck response of the BioRID P50F prototype resembled the female volunteer response corridors. The stiffness of the thoracic and lumbar spinal joints remained the same as the average sized male BioRID II, and therefore likely stiffer than joints of an average female. Consequently, the peak rearward angular displacement of the head and T1, and the rearward displacement of the T1, were lesser for the BioRID P50F in comparison to the female volunteers. The biofidelity of the BioRID P50F prototype thus has some limitations. Based on a seat response comparison between the BioRID P50F and the BioRID II, it can be concluded that the male BioRID II is an insufficient representation of the average female in the assessment of the dynamic seat response and effectiveness of whiplash protection systems.